The Use of Online Delivery Order for Import Activities at PT Mitra Dua Mandiri Logistic - Ghaza Tri Adhila; Nursya'bani Purnama (PT SOLUSI EDUKASI BERDIKARI, 2024)
The online delivery order system was designed to speed up the process of issuing delivery orders, improve services in Indonesia, and reduce costs. However, several challenges still exist in practice. This study aims to assess how online delivery orders impact the import activities of goods at PT Mitra Dua Mandiri Logistic. Using a quantitative approach, the research involved surveys (questionnaires) and interviews. For analysis, simple linear regression and T-tests were conducted, along with descriptive and inferential techniques. The study included 60 respondents, equally divided into 30 employees and 30 consumers who met specific criteria. The findings indicate that online delivery orders have a positive effect on import activities at PT Mitra Dua Mandiri Logistic. Specifically, the aspects of smooth flow, logistics costs, and service quality each contribute positively to these import activities.